Combination of Decadal Predictions and Climate Projections in Time: Challenges and Potential Solutions. Issue 15 (4th August 2022) - Befort, D. J.; Brunner, L.; Borchert, L. F.; O'Reilly, C. H.; Mignot, J.; Ballinger, A. P.; Hegerl, G. C.; Murphy, J. M.; Weisheimer, A.
Abstract: This study presents an approach to provide seamless climate information by concatenating decadal climate predictions and climate projections in time. Results for near‐surface air temperature over 29 regions indicate that such an approach has potential to provide meaningful information but can also introduce significant inconsistencies. Inconsistencies are often most pronounced for relatively extreme quantiles of the CMIP6 multi‐model ensemble distribution, whereas they are generally smaller and mostly insignificant for quantiles close to the median. The regions most affected are the North Atlantic, Greenland and Northern Europe. Two potential ways to reduce inconsistencies are discussed, including a simple calibration method and a weighting approach based on model performance. Calibration generally reduces inconsistencies but does not eliminate all of them. The impact of model weighting is minor, which is found to be linked to the small size of the decadal climate prediction ensemble, which in turn limits the applicability of that method. Plain Language Summary: Continuous and consistent information about the evolution of climate in next 1–40 years is crucial for the development of mitigation and adaptation strategies. Historically, scientific products providing weather and climate information have been designed for specific time scales, for example, seasonal or decadal climate predictions (1–10 years), or long‐term climate projections (1–100 + years). As a consequence, currently only climate projections can be used to provide continuous information beyond the 10 years time scale. However, as climate projections are not initialized using observations, they are likely – depending on the variable and region – less skillful than initialized predictions for shorter lead times. In this study we assess if meaningful continuous climate information can be obtained by concatenating decadal climate predictions and climate projections in time. Results suggest that significant inconsistencies (materialized in jumps in the resulting time series) can be introduced by this approach, however, for some regions temporal concatenation might provide meaningful climate information beyond decadal time scales. Furthermore, potential ways to reduce inconsistencies when concatenating are discussed. Key Points: Concatenating climate predictions and projections can introduce inconsistencies Concatenation is less problematic for quantiles close to the median compared to more extreme quantiles of the ensemble distribution A simple calibration method reduces but does not eliminate inconsistencies